Extremely stretchable strain sensors based on conductive self-healing dynamic cross-links hydrogels for human-motion detection - Cai, Guofa (2018)
Extremely stretchable self‐healing strain sensors based on conductive hydrogels are successfully fabricated. The strain sensor can achieve autonomic self‐heal electrically and mechanically under ambient conditions, and can sustain extreme elastic strain (1000%) with high gauge factor of 1.51. Furthermore, the strain sensors have good response, signal stability, and repeatability under various human motion detections.